1988
DOI: 10.1067/mva.1988.avs0080606
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysms and pseudoaneurysms of the superficial temporal artery caused by trauma

Abstract: Superficial temporal artery (STA) aneurysms as a result of trauma represent less than 1% of reported aneurysms. During the past 200 years only the type of trauma and the preferred treatment have significantly changed. Patients are generally young men with a recent history of blunt head trauma. They may complain of a mass, headache, or other vague symptoms. Neurologic defects are rare; however, if a neurologic deficit exists, the physician should consider either arteriography or a head CT scan to search for int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 0 publications
1
59
0
12
Order By: Relevance
“…4) Traumatic STA aneurysm usually develops in young adult men at 2 to 6 weeks after blunt head trauma, 11) and the majority are pseudoaneurysms. Spontaneous or non-traumatic STA aneurysms are quite rare, with only 16 cases described.…”
Section: Introductionmentioning
confidence: 99%
“…4) Traumatic STA aneurysm usually develops in young adult men at 2 to 6 weeks after blunt head trauma, 11) and the majority are pseudoaneurysms. Spontaneous or non-traumatic STA aneurysms are quite rare, with only 16 cases described.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% occur in men usually aged 20-40 years. 3 A review of STA aneurysms by Peick et al 3 found that of 174 cases, 90% were caused by trauma. Uchida and Sakuma 4 found only 9 cases (18.8%) were true aneurysms with only single cases of congenital, arterial dissection, and atherosclerotic aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as many as 20% of patients present anywhere from 6 months to 4 years after their injury. 13 In view of the variability in the time to presentation, a thorough history is important. As in our case, traumatic pseudoaneurysms can be easily misdiagnosed, particularly if they present with skin discoloration and are tender to palpation.…”
Section: Presentationmentioning
confidence: 99%